PENGARUH SOSIALISASI DAN PEMAHAMAN INSENTIF PAJAK TERHADAP KEPATUHAN WAJIB PAJAK PADA MASA PANDEMI COVID-19 : Studi Pada Pemilik UMKM Di Kota Bekasi - Nazzira Rasya Fazriputri (2021)
This research is a quantitative research, where this study aims to analyze the effect of socialization and understanding of tax incentives on taxpayer compliance. The population used in this study, were taxpayers who own MSMEs in Bekasi City, for this population, the sampling technique used is simple random sampling with a sample of 108 MSME taxpayer respondents in Bekasi City. The technique used to analyze the data is by using the Partial Least Square (PLS) method. Based on the tests carried out, the results show that (1) socialization understanding of tax incentives have a positive significant effect on taxpayer compliance, (2) understanding of tax incentives have a positive significant effect on taxpayer compliance and (3) socialization of tax incentives have a positive significant effect on understanding of tax incentives.